The Effect of Health Service Quality on Patient Satisfaction of BPJS Outpatient Installation at Prima Inti Medika Hospital, Dewantara District, North Aceh - Nur, Muhammad Ludhy; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
Problems that may affect patient satisfaction in basic health services, including the appearance of the hospital building is convincing and attractive, the hospital environment is clean and comfortable, the hospital is open on time, the seats where the turn is available are sufficient, the staff greets politely, is friendly and wants to help, the health worker listens to the patient's complaints, the health worker checks carefully and thoroughly,  Health workers provide complete information, medicines needed by patients are available at the hospital. The purpose of this study is to determine the effect of outpatient health services on the satisfaction of BPJS Kesehatan participants. This type of research is an analytical survey with a cross sectional approach using primary data with questionnaires and secondary data from the report of Prima Inti Medika Hospital North Aceh. The population in this study is all outpatients of BPJS Kesehatan participants who visited Prima Inti Medika Hospital as many as 1,120 people with a sample of 95 people determined using the acidental sampling method. The analysis used univariate, bivariate and multivariate analysis. The results of the chi square test showed that responsiveness (p= 0.001 < 0.05), reliability (p= 0.000< 0.05), assurance (p= 0.002< 0.05), concern (p= 0.000 <0.05) and physical evidence (p= 0.060 > 0.05). The logistic regression test showed that the most influential variable on patient satisfaction was concern with an Exp (B) value of 4.781. The conclusion of this study is that there is an influence of responsiveness, reliability, assurance, and care have a relationship with patient satisfaction, while physical evidence has no relationship with patient satisfaction. Efforts are needed to improve the quality of outpatient services by increasing a sense of full attention, quick response to patient problems, not discriminating between patients and others, being able to provide a good response in responding to patient complaints in order to establish a harmonious relationship between health workers and patients in order to achieve services that are able to satisfy patients.